2022
DOI: 10.1039/d1nr07353b
|View full text |Cite
|
Sign up to set email alerts
|

Few-layer Mg-deficient borophene nanosheets: I2 oxidation and ultrasonic delamination from MgB2

Abstract: By using I2 as the oxidant and CH3CN as reaction medium, few-layer Mg-deficient borophene nanosheets (FBN) with a stoichiometric ratio of Mg0.22B2 is prepared by oxidizing MgB2 in a mixture...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For instance, exfoliated layered MgB 2 yields Mgdeficient BNSs. Our group utilized I 2 as the oxidant and acetonitrile/HCl as the reaction medium to prepare Mgdeficient borophene nanosheets (FBN), 99 as shown in Figure 6c. The fabricated FBN exhibits a 2D sheet-like morphology with an average thickness of 4.14 nm and a transverse size of 500 nm, and demonstrates good crystallinity corresponding to rhombohedral boron, with a maximum Mg removal rate of up to 78%.…”
Section: Two-dimension (2d) Boron Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, exfoliated layered MgB 2 yields Mgdeficient BNSs. Our group utilized I 2 as the oxidant and acetonitrile/HCl as the reaction medium to prepare Mgdeficient borophene nanosheets (FBN), 99 as shown in Figure 6c. The fabricated FBN exhibits a 2D sheet-like morphology with an average thickness of 4.14 nm and a transverse size of 500 nm, and demonstrates good crystallinity corresponding to rhombohedral boron, with a maximum Mg removal rate of up to 78%.…”
Section: Two-dimension (2d) Boron Nanomaterialsmentioning
confidence: 99%
“…(c) Preparation process illustration and morphology distribution (SEM and AFM) images of Mg-deficient BNSs prepared by I 2 oxidation and ultrasonic delamination . Reproduced with permission from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Preparation and Properties Of Mono-element Boron Nanomaterialsmentioning
confidence: 99%
“…Xiao et al recently reported a method to synthesize MXene-like MgB 2 nanosheets where the bulk powder was ultrasonicated in DI water followed by etching using HCl . Very recently, Zhang et al adopted an ultrasound and oxidation assisted liquid-phase approach to delaminate MgB 2 into nanosheets . In this work, bulk MgB 2 was dispersed in a mixture of acetonitrile and hydrochloric acid and I 2 was used as an oxidizer.…”
Section: Magnesium Diboride (Mgb2)mentioning
confidence: 99%
“…37 Very recently, Zhang et al adopted an ultrasound and oxidation assisted liquid-phase approach to delaminate MgB 2 into nanosheets. 38 In this work, bulk MgB 2 was dispersed in a mixture of acetonitrile and hydrochloric acid and I 2 was used as an oxidizer. The authors state that this process led to the oxidation of MgB 2 , however the process had to be carried out for 14 days.…”
Section: Liquid-phase Exfoliationmentioning
confidence: 99%